Improving the Skills of the Subak Giri Kusuma Tirta Group in Mengani Village, Bangli, in Processing Waste into Quality Organic Fertilizer - Astiari, Ni Komang Alit; Sutapa, I Gede; Suaria, I Nengah; Andriani, Anak Agung Sagung Putri Risa; Rama, Kade Nusde Sari (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This community service program aimed to empower the